Role of Color Doppler Ultrasonography in Evaluation of Extracranial Carotid Artery in Stroke Patients: A Prospective Study - Yadav, Ajay Kumar; Dev, Binit; Taparia, Sushil; Yadav, Neha; Upadhyaya, Bishal Babu; Kumar, Parvez; Mandal, Rakesh; Rajbanshi, Lalit Kumar (Birat Journal of Health Sciences, 2020)
Introduction: Stroke is life threatening & debilitating neurological disease, defined as focal neurological deficit of sudden onset lasting >24 hours & vascular in origin. Significant association between ischemic type of stroke with carotid artery disease seen, more prevalent with carotid artery stenosis. Objectives: This study was done to show association between extracranial carotid artery disease & cerebrovascular accidents (CVAs) with the help of Color Doppler Sonography (CDS). The association between carotid artery disease with associated risk factors were also assessed. Methodology: In this ethically approved prospective study, carotid CDS was done in 79 consecutive patients with diagnosis of acute ischemic stroke (AIS). The various parameters studied included peak systolic velocity (PSV) of internal carotid artery (ICA) & common carotid artery (CCA), ICA/CCA PSV ratio & plaque characteristics. The data collected was analyzed with appropriate statistical test of significance was calculated. Results: Total 79 patients with AIS included out of which 53 were males & 26 were females. The most common presenting complains were hemiparesis (30.4%) & most commonly associated risk factors included hypertension (62.02%). Right sided strokes were most common (44.3%) & middle cerebral artery was most commonly involved vascular territory. Significant stenosis (≥50%) of carotid artery was seen in 27 patients with ICA most common site (45.8%) for plaque formation. Bilateral carotid artery involvement (52.1%) with hypoechoic echotexture of atheromatous plaques (46.6%) was most responsible for significant stenosis & increased intima media thickness. Increased value of PSV & EDV was seen in the stenotic area in the proportion of stenosis with increased PSV ICA/CCA ratio of more than three indicates >60% stenosis. Conclusion: The present study showed well documented role of carotid doppler in detection of site & extent of carotid artery stenosis due to atheromatous plaques of various characteristics playing critical role in thromboembolic phenomenon responsible for development of stroke.